(الدكتور والبصير والصبور) "السيرة والإنجازات والعلاقات" - د. أحمد بن مهني مصلح (Sharwes Scientific Journal, 2025)
After an introduction in which I present the history of Nafusa, the ancientness of its cities, the richness of its heritage, and its ancient relations with the Ibadi citizens, I briefly introduce myself to the birthplace of Dr. Muhammad Ali Janboula, Al-Basir Abdullah Masoud Hanboula (Al-Rahibat), the visitation of Dr. Abdullah’s stable, and the land of Saboor, Amr Masoud Abu Al-Qasim. Prolonged, its people know better. In the first section, I will simplify the biography of Dr. Muhammad Ali Janboula from birth to death: his upbringing and the stages of his studies from primary school to university through his communication with Al-Zaytouna in Tunisia, and Ain Shams University in Cairo, and his preparation for his doctorate there. I show him his residence in the Buffalo Agency, in Cairo, his brief trip to France, then his return as an advisor to his homeland, and his most prominent achievements, presenting my correspondence with him, and his relationships, guided by With the sleeper’s hammocks, then he died. In the second section, I review the biography of Dr. Sheikh Abdullah Masoud Hanboula from his birth to his death: His upbringing and stages of study, including his journey to seek knowledge in Djerba, then at the Zaytouna Mosque in Tunisia and Al-Azhar in Egypt His return to Al-Zaytouna to prepare for his master’s degree, his relations with those who dealt with him in the East and West, and his return as a preacher. Bozoara, his achievements, and the tribulations and illnesses he endured and endured until his death .In the third section, I present the biography of the patient Sheikh Amr Masoud Abu Al-Qasim Al-Kabawi from his birth Until his death: his upbringing, the stages of his studies, and his journey to gain knowledge in Al-Jabal and Tripoli. And I follow His achievements, his literary and legal effects, and his relations with visiting the people of Djerba, the people of Mizab, and the libraries in them. He was subjected to imprisonment and was patient with the trials, then he died and lost Kabao and the whole mountain.